The abortion as a social and medical problem of present generation - Konkabaeva, А.Е.; Kystaubaeva, Z.Т.; Akhmetova, М.Zh. (Ye.A.Buketov Karaganda State University Publish hous, 2012)
One of the most relevant, important and controversial problems of public life, politics and morality is abortion. The abortion and leading position in the structure of reproductive losses and the health of women of childbearing age is medico-social and contested issue in nowadays. Abortion as a whole remains the traditional method of regulation of reproductive behavior. Artificial abruption of life is a fundamental problem of human being, increasing interest in the article. This paper examines the effects that significantly impairs the reproductive system and serious complications for women's reproductive function after abortion, including maternal mortality. Showing prevention and solutions.
Жасанды түсік қазіргі заманның қоғамдық жəне медициналық мəселесі ретінде
Аборт как социально-медицинская проблема нынешнего поколения
Keywords: reproductive health; reproduction; reproductive age; the abortion; reproductive losses; medical; pregnancy; pregnant; women; sex; teenage girls